Analysis of the Use of Financial Technology and Finan-cial Literacy among MSMEs - Novia Utami (Politeknik Negeri Bengkalis, 2023)
The massive effects of the Covid-19 pandemic and continuous technological innovations are not the only ones that change people’s lives; the world is now experiencing the emergence of FinTech. FinTech is technology-based financial services that allow financial transactions to be made easily, anywhere and anytime. FinTech has given MSMEs advantages, from capital financing to easy transaction processes to boost MSMEs’ growth. This research aims to see how adoption of FinTech and financial literacy affect the development of Indonesia’s MSMEs. Data were using online questionnaires while samples were selected using convenience sampling technique with 125 business owners participating in this research. Data were then analyzed using OLS regression method. Results suggest that FinTech and financial literacy have a positive and significant influence on the development of MSMEs.